The different immune profiles of normal colonic mucosa in cancer-free Lynch syndrome carriers and Lynch syndrome colorectal cancer patients - Bohaumilitzky, Lena; Kluck, Klaus; Hüneburg, Robert; Gallon, Richard; Nattermann, Jacob; Kirchner, Martina; Kristiansen, Glen; Hommerding, Oliver; Pfuderer, Pauline Luise; Wagner, Lelia; Echterdiek, Fabian Friedrich; Kösegi, Svenja; et al. (Gastroenterology, 2022)
Due to the high load of immunogenic frameshift neoantigens, tumors arising in individuals with Lynch syndrome (LS), the most common inherited colorectal cancer (CRC) syndrome, are characterized by a pronounced immune infiltration. However, the immune status of normal colorectal mucosa in LS is not well characterized. We assessed the immune infiltrate in tumor-distant normal colorectal mucosa from LS CRC patients, sporadic microsatellite-unstable (MSI) and microsatellite-stable (MSS) CRC patients, and cancer-free LS carriers.
Available online 2 December 2021
Gesehen am 24.02.2022